VISITORSâ BEHAVIOR OF THE USE OF GREEN OPEN-SPACE IN THE URBAN ENVIRONMENT. CASE STUDY: TAMAN MALUKU - BANDUNG - Thalib Raihan, Muhammad
A park is one of the green open spaces in the urban environment that can be used for a variety of recreational and social activities, either individually or collectively. Every urban park has a close relationship between users with various motivations. In addition, a park serves as a gathering place for users with different needs. Consequently, while experiencing a space, visitors have their own assessment of the space’s characteristics based on a certain condition. If the relationship between visitors and their motives is fit with the surrounding amenities, it can bring the aliveness of urban parks. The purpose of this study is to gain a better understanding of the role of urban parks as green open-spaces by evaluating visitors' motivations, the attractiveness of amenities, and the relationship between the users’ characteristics and a series of activities. In 2013, the mayor of Bandung initiated a program to revitalise urban parks. Taman Maluku is one of twenty-nine parks that have been revitalized. Taman Maluku was once used as a place to relax for visitors to Jabbeurs, the annual market held in front of the park. Taman Maluku is currently free and open to the public on a daily basis. The park has amenities, such as benches, pedestrian paths, and a playground, that encourage people to participate in activities. As a result, the park is suitable for a research study. This study attempted to evaluate the attractiveness and impact of Taman Maluku’s amenities and green attributes. Visitors are concerned with park characteristics that are generally associated with amenities and green environments that involve visual connections based on biophilic theory, such as the need for visibility and closure (prospect-refuge), and mystery aspects that are associated with the characteristics of spaces that invite curiosity and challenge. In addition, it involves non-visual connections, such as thermal conditions, sound, and attractiveness that are generally unconnected to vision. The data collection instrument used an online questionnaire through QRC and the snowball method in May 2021. After validating the questionnaire responses, 100 samples of 116 data were obtained. Data processing using descriptive analysis and content analysis for open-ended questions, incorporating visitor experience responses and points of interest. Then a quantitative analysis was conducted to find out the demographic distribution of each detail of visits and activities in Taman Maluku. Research findings indicate that respondents visit Taman Maluku to relieve fatigue from their daily routine. The proportions of male and female users are nearly similar, and they have a preference for the atmosphere that is supported by natural attributes, providing better shading, air quality and noise. The main factor of the visits is influenced by the atmosphere in the Maluku Park environment, which supports cool thermal conditions, tranquillity, and natural/landscape views. Generally, visitor exploration occurs in more open areas and easily accessible to the outer environment of the park, particularly the western and southern park boundaries. Visitors preferred more expansive and spacious areas that supported the characteristics of a space with high-prospect and low-refuge. The use of the area in the middle of the park is generally less. In addition, there are issues related to the negative experience of visitors in high-density and hidden inner spots which are identical to the mystery aspects and less desirable to explore. Based on clusters, the characteristics of Taman Maluku usage may be categorized into two groups of behaviour: the relaxing activity group and the athletic activity group. The needs of the relaxation activity group tend to relax, interact and enjoy the surrounding environment. While the athletic activity group is more active and has a variety of sports activities, it tends to require more planning and preparation for hobbies or pleasure activities. The significant difference between the two groups was influenced by the allocation of leisure time and social factors, including duration, visiting hours, and number of person to accompany. The results of this study are then used to improve the design of parks so that they can meet the needs of the whole community in the best possible way.